Program Madrasah Diniyah dalam Meningkatkan Pengetahuan Siswa pada Materi Kitab Ro’sun Sirah di Desa Butuh - Linda Lailatul Rohmah; Khoirotul Izzah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Indonesia is one of the largest Muslim countries in the world. So that the existence of Arabic in Indonesia becomes one of the important languages to be studied and mastered by Indonesians. Therefore, Arabic has been taught in various educational institutions, especially Islamic religious education institutions in Islamic schools as well as in boarding schools. Various Arabic books are taught to students in pesantren, one of which is the Arabic Book of Ro'sun Sirah. The Book of Ro'sun Sirah is a mufrodat in Arabic which is interpreted in Javanese. In this study the author will discuss about the material in the book of Ro'sun Sirah, as well as the methods taught to students to learn the book. The Book of Ro'sun Sirah consists of 9 chapters, 76 nadzom and 304 vocabulary. In the book designed for entry-level students in the form of simple nadhom. The choice of nadhom form is very commonly implemented in Islamic religious education institutions (Pondok Pesantren and Madrasah Diniyah). The nadzom form has three functions: (1) entertainment function, (2) educational and teaching function, and (3) spiritual function. The type of method used in this report is PAR (Participation Action Research). The purpose of this study was to introduce arabic vocabulary or mufrodat that was repersed into Javanese to the students of The Village of Need. The result obtained from the activities of this PKM Research Program is that children become aware of vocabulary in Arabic.